ICT Digital Teaching Module on the Preparation of Interactive Student Worksheets - Yusi Elviani; Gede Wawan Sudatha (Mimbar Ilmu, 2023)
Problems with ICT teaching modules that are still conventional and the lack of optimal use of technology causes students difficulties in learning. This study aims to develop digital teaching modules in ICT courses with Interactive LKPD preparation material. This research is a development research carried out using the ADDIE model. The subjects of this research are experts and practitioners, while the objects of this research are digital modules. In this study, data collection was carried out using a questionnaire by providing assessment sheets to experts and practitioners. The research instrument is a questionnaire. The data analysis technique uses descriptive qualitative analysis. The result of the research is the score validity content validity score of the material expert is 90% with very good qualifications, the media expert validity score is 92% with very good qualifications, and the design expert validity is 92% with very good qualifications. The achievement level of digital module practitioners is 94%, with very good qualifications; on the individual test, it is 97%, with very good qualifications, and on the small group test, it is 98%, with very good qualifications. Based on the validity and practicality of test results, digital ICT teaching modules in preparing interactive worksheets are interpreted as feasible and practical to use. with very good qualifications. Based on the validity and practicality of test results, digital ICT teaching modules in preparing interactive worksheets are interpreted as feasible and practical to use. with very good qualifications. Based on the validity and practicality of test results, digital ICT teaching modules in preparing interactive worksheets are interpreted as feasible and practical to use.